The devaluation of the Finnish mark in 1967 - G. MATTSON (PSL Quarterly Review, 2014)
Criticism of the adjustable peg system of international payments is mounting and well-known economists have gone as far as to deny that devaluation can have positive results in the modern world. Accordingly, the present article examines the latest devaluation of the Finnish mark which took place in October 1967 and was by about 24 percent. After briefly touching on the factors which led to Finland’s serious balance-of-payments deficit, the author discusses the main components in the measures which accompanied the devaluation, with particular attention to the “sliding” export levy and the incomes policy. The results obtained by the end of 1969 in terms of growth, employment, external balance and price stability are then described and the reasons for the apparent short-term success of this experiment are evaluated.